1997
DOI: 10.1046/j.1365-3083.1997.d01-381.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4 Synergizes with IL‐10 and Anti‐CD40 MoAbs to Induce B‐Cell Differentiation in Patients with Common Variable Immunodeficiency

Abstract: Punnonen J, Kainulainen L, Ruuskanen O, Nikoskelainen J, Arvilommi H. IL-4 Synergizes with IL-10 and Anti-CD40 MoAbs to Induce B-Cell Differentiation in Patients with Common Variable Immunodeficiency. Scand J Immunol 1997;45:203-212 In the present study the phenotype and function of lymphocytes from patients with common variable immunodeficiency (CVI) were studied. Five out of 12 patients had abnormally low proportion of CD4 + T cells, but PBMC of these patients were capable of proliferating in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…We analysed the PBMC population, and showed that combinations of anti-CD40 and various cytokines (IL-2, IL-4 and IL-10) were unable to induce significant IgG production in all but one CVI case. Similar data were recently published by Punnonen et al [26] who measured induction of IgG secreting cells (rather than Ig production) in PBMC from CVI patients. These authors showed that triggering of CD40 in the presence of IL-10 was completely ineffective in inducing Ig-secreting cells, while B-cell differentiation could be obtained on CD40 stimulated cells, by the addition of both IL-4 and IL-10.…”
Section: Discussionsupporting
confidence: 87%
“…We analysed the PBMC population, and showed that combinations of anti-CD40 and various cytokines (IL-2, IL-4 and IL-10) were unable to induce significant IgG production in all but one CVI case. Similar data were recently published by Punnonen et al [26] who measured induction of IgG secreting cells (rather than Ig production) in PBMC from CVI patients. These authors showed that triggering of CD40 in the presence of IL-10 was completely ineffective in inducing Ig-secreting cells, while B-cell differentiation could be obtained on CD40 stimulated cells, by the addition of both IL-4 and IL-10.…”
Section: Discussionsupporting
confidence: 87%
“…These finding suggest an hierarchy in the synthesis of isotypes and subclasses that seem to correspond to the location of the heavy chain gene in the human genome on chromosome 14 (Nonoyama et al 1993). The same phenomena was confirmed by other studies but using bacterial polysaccharides and cytokines as the stimulants for antibody produc- tion (Eisenstein et al 1994, Eisenstein and Strober 1995, Punnonen et al 1997. Histologically, lymphoid tissues from most CVID patients have normal B cell differentiation areas, suggesting that these cells are capable of recognizing antigen on a primary encounter and reinforcing the notion that the defect is associated with terminal stages in the differentiation cascade.…”
Section: B Lymphocytes In Cvidsupporting
confidence: 72%
“…In contrast, monocyte-derived IL-10 has been implicated in the diminished production of IL-2 by some patients and as a contributor to the proliferative deficit observed in a subset of individuals with CVID (Zhou et al 1998). Interestingly, the effect of IL-10 on IL-2 synthesis by T lymphocytes from CVID patients and its effect on antibody synthesis in vitro was only observed in the presence of IL-4 and anti-CD40 antibody but not in the absence of IL-4 (Punnonen et al 1997). It is noteworthy that defects on IL-2 production have also been described independently from the interaction with other cytokines (Fischer et al 1993.…”
Section: T Lymphocytes In Cvidmentioning
confidence: 99%
“…There have been reports on defect production of IL-10 in B cells from CVID patients (15), and IL-10 deficiency was suggested to be part of the etiology of the disease (32,33). Taken together with our recent findings that IL-10 is required both for RA-induced proliferation and IgG production in normal B cells stimulated with CpG and anti-RP105 (12), it was interesting to find that the defects in IL-10 secretion from CVID-derived B cells were less pronounced than the nearly complete absence of IgG secretion from the same cells and that, to a large extent, RA was able to restore the deficient TLR9/RP105-mediated IL-10 secretion from the cells.…”
Section: Discussionmentioning
confidence: 99%